Development of Smartphone-Based Athlete Physical Fitness Applications During Work From Home - Azhar Riau Pamungkas; Ni Putu Nita Wijayanti; Aref Vai; Ittaqwa Ittaqwa (Journal of Coaching and Sports Science, 2022)
Developing exercise equipment is one way to modify the fitness training concept. This research focused on developing a smartphone-based physical fitness exercise program for athletes working from home during the Covid-19 pandemic. The approach used was a descriptive procedural model, which identified the procedures that must be carried out to make a product. Quantitative and qualitative data were used in this study. The results showed that the approval rating of the practical category was 93% from material experts and 92 percent from media experts. The application has eight fitness movements, including warming up, sit up, plank, wall sits, push up, back up, lunges and squats. The application is available and can be downloaded on the Google Play Store for android users. It can produce effectiveness and influence the users by reminding them to exercise at home. This application is ready to be used by the community, with a small group trial result of 93.2 percent and a large group trial result of 86.1 percent. This application is a breakthrough for coaches to develop athletes' physiques during a pandemic to exercise at home.